Long‐term results of high‐dose imatinib in children and adolescents with chronic myeloid leukaemia in chronic phase: the Italian experience. (20th April 2015) - Giona, Fiorina; Putti, Maria C.; Micalizzi, Concetta; Menna, Giuseppe; Moleti, Maria L.; Santoro, Nicola; Iaria, Grazia; Ladogana, Saverio; Burnelli, Roberta; Consarino, Caterina; Varotto, Stefania; Tucci, Francesca; et al.
Summary Imatinib mesylate (IM) is used for the management of childhood chronic myeloid leukaemia (CML). The most effective dosage of IM and its long‐term efficacy in children are not well defined. The purpose of this multicentre study is to report on the long‐term results of high‐dose IM (340 mg/m2/d) in CML patients in chronic phase (CP‐CML) aged <18 years at diagnosis. A total of 47 CP‐CML patients with a median age at diagnosis of 11 years 9 months were enrolled in nine Italian centres. Complete cytogenetic response was achieved in 91·5% of the evaluable patients at a median time of 6 months. BCR‐ABL1 International Scale ≤ 0·1% (major molecular response; MMR) and ≤0·01% (molecular response; MR) at 12 months were 66·6% and 33%, respectively. During follow‐up, MMR and MR were achieved in 78·6% and 61% of children, respectively. IM was safely discontinued in 3 long‐term treated children with a durable MR. Twelve patients (eight cytogenetic/molecular responders) underwent stem cell transplantation. The progression‐free survival probabilities at 96 months for responding patients who continued IM and for those transplanted were 60% and 50%, respectively. After a median follow‐up of 52 months (range 3–146), all patients are alive. High‐dose IM is a long‐term effective therapy in children and adolescents with CP‐CML.